Antecedents of Patients’ Revisit Intention at Siloam Hospitals Kebon Jeruks - Martin Hendrata; Zoel Hutabarat (Greenation Publisher & Yayasan Global Research National, 2026)
This study aims to analyze the factors influencing patient revisit intention at RS Siloam Hospitals Kebon Jeruk, focusing on service quality, additional factors, hospital physical environment, and trust, and their impact on patient satisfaction and revisit intention. The research was conducted using survey data from 160 outpatient patients, analyzed using the Partial Least Squares - Structural Equation Modeling (PLS-SEM) method. The results indicate that service quality factors, including reliability, responsiveness, and empathy, significantly affect patient satisfaction. Additionally, hospital physical environment and trust also positively contribute to patient satisfaction. Patient satisfaction, in turn, significantly influences patient revisit intention. The Importance-Performance Matrix Analysis (IPMA) identified that Trust and Hospital Physical Environment, though highly important, have relatively low performance and require more attention. Conversely, patient satisfaction is at a good level and should be maintained. These findings provide managerial implications for RS Siloam Hospitals Kebon Jeruk to improve aspects influencing patient satisfaction, particularly trust and physical environment, to enhance patient loyalty and strengthen revisit intention. This study also opens opportunities for further research by expanding the sample to include multiple hospitals to strengthen the generalizability of the findings.